ANALISIS PELAKSANAAN MODEL PEMBELAJARAN PREDICT OBSERVE EXPLAIN (POE)BERBANTUAN e-LKPD DAN KORELASINYA DENGAN KETERAMPILAN PROSES SAINS PESERTADIDIK PADA MATERI ASAM BASA (Jurnal Sains dan Matematika, 2024)
The learning process requires a model that enhances student interaction and science process skills. One effective approach is the Predict-Observe-Explain (POE) model. This study aims to analyze the implementation of the e-LKPD-assisted POE model in acid-base material and its correlation with students' science process skills in class XI IPA at SMAN 4 Jambi City. This research employs a mixed-method approach using a concurrent triangulation model. The sampling technique used was purposive sampling, specifically selecting class XI IPA 5. Data collection instruments included observation sheets for evaluating the implementation of the POE model by both teachers and students, as well as observation sheets assessing students' science process skills. Pearson’s product-moment correlation test was conducted to determine the relationship between the POE model implementation and students’ science process skills. The findings indicate that the implementation of the POE model by students reached 74.26%, categorized as good, while students’ science process skills scored 70.92%, also in the good category. The correlation analysis showed a strong relationship between the POE model implementation and students' science process skills, with rxy = 0.86, indicating a very strong correlation, and r² = 74%, reflecting a significant contribution. Based on these results, it can be concluded that the e-LKPD-assisted POE model is positively correlated with students' science process skills in acid-base material in class XI IPA at SMAN 4 Jambi City.